An investigation into rainfall characteristics in peninsular Malaysia using copulas method - Mohd Faris, Fauzi (2021)
Extreme rain patterns are influenced by variations in daily rain. Floods, landslides, and crop failures are all caused by excessive rain. Physical damage to residential and other structures can be caused by floods. As a result, efforts must be made to mitigate the impact of loss caused by heavy rain. Estimating the huge damage to the floods arising from excessive rainfall is one of the efforts to limit this effect. Flood loss modeling can be used to estimate how much damage will occur when floods occur due to heavy rain. For modeling, extreme value theory and copula methods are used. Copula is a function that combines the multivariate distribution function to the marginal distribution function. The Extreme Value Theory focuses on modeling of the tail behaviour of a distribution using only extreme values rather than the whole dataset, it can potentially provide a more accurate estimate of tail risk. Based on the modelling results, from 30 stations, Frank Copula recorded 17 stations, so we chose Frank Copula is the best Copula model to explain the relationship between severity and duration or rainfall in Peninsular Malaysia. When the parameter value of both low or strong variables, Copula Frank explains close relationships.